ARTISTIC COMPOSITE FORM CREATION OF «UKRZALIZNYTSIA» CORPORATE CLOTHES: AESTHETIC ASPECT - Колосніченко, О. В.; Приходько-Кононенко, І. О.; Остапенко, Н. В.; Колосніченко, М. В. (Art and Design, 2019)
The goal of the research is to develop the bases of artistic composite form creation and stylistic series aesthetics of «Ukrzaliznytsia» employees’ uniforms. There have been considered the peculiarities of approaches to the uniform (special purpose clothes) design as an integral part of the material culture, compliance with the provision of its aesthetic, identification, stylistic and image corporation requirements. Historical, functional, comparative, associative and systematic research methods have been applied. Also there have been used comparative and typological, analytical and empirical approaches. Results. There has been performed an analysis of the mutual influence peculiarities of technology and morphology of the special purpose clothes development indicating aesthetic and cultural aspect. The uniform has been studied in the context of the main element of corporate culture and ethics, social phenomenon. The dilemmas of the features creating a women's uniform as an eclectic quasi-male and feminized typology have been determined. Scientific novelty. The information has been systematized as for identifying the trend lines in the uniform development and determining the trend of future developments. Constructivism has been defined as the theoretical basis for the origin and development of the design of modern special purpose clothes, as well as clothing as a cultural object in general. There has been proved historical influence of uniform clothes, uniforms on the development of modern fashion. Practical significance. The range structure of corporate clothes for «Ukrzaliznytsia» employees has been created. There have been offered varieties of special purpose clothes, which consist of departmental uniforms, working clothes and special clothes in accordance with the working conditions. The uniform clothes kits for train hosts have been developed, their compositional and constructive arrangement has been proposed. The color solution has been offered and the compatibility of clothes with shoes and accessories has been taken into account in order to create the figurative uniformity in accordance with the «Ukrzaliznytsia» corporate style.